Advancing inclusion in sports for students with disability: A mixed-methods study on awareness and perspectives toward adaptive sports - Monira I. Aldhahi; Bodor H. Bin sheeha; Noura I. Alothman; Reem M. Basuodan; Reem A. Alabdulwahab (PLoS ONE, 2026)
Adaptive sports promote inclusion, participation, and well-being in individuals with disabilities. However, limited research has examined the knowledge, awareness, and perceptions of adaptive sports, as well as institutional support and barriers within Saudi universities. An explanatory sequential mixed-methods design was employed. A cross-sectional survey (n = 350; 18.29% reported disabilities; 70.57% females; mean age 28 ± 11 years) assessed knowledge, awareness, perceptions, and perceived barriers to adaptive sports among students, faculty, and administrative staff. Survey findings informed purposive sampling for the qualitative phase, which included focus group discussions with faculty and semi-structured interviews with students with disabilities (SWDs) to contextualize quantitative patterns. The qualitative phase included a focus group discussion, and six interviews were conducted virtually using Microsoft Teams. Participants demonstrated uneven knowledge of adaptive sports (mean score: 8/16). While most correctly recognized their role in enhancing physical education and promoting participation through adapted equipment (>83%), but low understanding of classification (19.71%) and healthcare roles (30.57%). Awareness was low across all domains, particularly in training (75.71% unaware) and participation (80.57% unaware), indicating significant gaps in exposure and education. Although most participants recognized the benefits of adaptive sports, they noted the lack of sufficient policies, accessible facilities, promotion, and staff support. Less than 30% reported inclusive programs, and 16.29% perceived equal funding for parasports training. The key barriers included a lack of awareness (43.14%), inaccessible facilities (41.42%), and limited resources (40%). Interviews with students with disabilities and focus groups with faculty and specialists revealed positive experiences, emphasizing personal growth and social inclusion, but also identified challenges in infrastructure, recruitment, and policy. Despite favorable perceptions, substantial gaps persist in knowledge, accessibility, and institutional commitment. Addressing these issues through awareness campaigns, improved facilities, and inclusive policy development is vital for advancing adaptive sports participation and fostering a culture of inclusion in Saudi higher education.